(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting reproductive-aged women and is associated with metabolic, reproductive, and psychological complications. Lifestyle factors such as diet, physical activity, sleep, and stress are known to influence the development and severity of PCOS. This study aimed to determine the prevalence of PCOS and identify its lifestyle determinants among female university students. Methods: A cross-sectional study was conducted among 246 female students aged 18–30 years from selected university in Lahore, Pakistan. Participants completed a structured self-administered questionnaire assessing socio-demographics, menstrual and clinical history, and lifestyle behaviours, including diet, physical activity, sleep, and stress. PCOS was defined based on self-reported physician diagnosis or presence of at least two features according to the Rotterdam criteria. Descriptive statistics summarized participant characteristics and PCOS prevalence. Associations between lifestyle factors and PCOS were analysed using chi-square tests and multivariable logistic regression. Results: The prevalence of PCOS was 21.1% (n = 52). Overweight/obesity, low physical activity, frequent fast food consumption, short sleep duration (<6 hours), and high perceived stress were significantly associated with PCOS (p < 0.05). Multivariable logistic regression indicated that overweight/obese participants had 2.7 times higher odds of PCOS (AOR: 2.7; 95% CI: 1.4–5.1), low physical activity (AOR: 2.2; 95% CI: 1.1–4.2), frequent fast food intake (AOR: 2.9; 95% CI: 1.5–5.5), short sleep (AOR: 2.4; 95% CI: 1.2–4.6), and high stress (AOR: 3.2; 95% CI: 1.7–6.0). Conclusions: PCOS is prevalent among female university students, and modifiable lifestyle factors including obesity, sedentary behaviour, unhealthy diet, insufficient sleep, and high stress are significant determinants. Early awareness, screening, and targeted lifestyle interventions are recommended to prevent and manage PCOS in this population.